2022
DOI: 10.1186/s12913-022-08824-3
|View full text |Cite
|
Sign up to set email alerts
|

Burden of informal caregivers of people without natural speech: a mixed-methods intervention study

Abstract: Background People with disabilities and without natural speech often rely on care provided by informal caregivers. The caregiving situation of these informal caregivers has been poorly researched. The objectives of the study are 1) to identify stressors, resources, and coping strategies among informal caregivers of people without natural speech and 2) to examine whether a complex intervention in augmentative and alternative communication (AAC) that is not primarily tailored to the needs of info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Caring for an individual with LIS can yield a variety of new challenges. Caregivers can often be impacted by a variety of stressors, such as limited or lack of communication with the patient, limited support from loved ones, a large burden of daily responsibilities, a lack of resources for support and information, financial stressors, role change, or isolation [22]. Of note, Zinkevich et al found that caregiver burden is significantly reduced with the implementation of successful AAC interventions.…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Caring for an individual with LIS can yield a variety of new challenges. Caregivers can often be impacted by a variety of stressors, such as limited or lack of communication with the patient, limited support from loved ones, a large burden of daily responsibilities, a lack of resources for support and information, financial stressors, role change, or isolation [22]. Of note, Zinkevich et al found that caregiver burden is significantly reduced with the implementation of successful AAC interventions.…”
Section: Caregiver Burdenmentioning
confidence: 99%